Transnationalism in Irish literature and culture - Parsons, Cóilín (Cambridge University Press, 2024)
Transnationalism in Irish Literature and Culture offers a wide-ranging set of essays exploring the travels of Irish literature and culture over the last century and more. The essays focus on writers and artists whose work has been taken up and re-read overseas; on cultural producers who have engaged with transnational scales in their work; and on critical practices that pay attention to comparative, global, and planetary dimensions of Irish literature and culture. Nation and territory have long been central to cultural production in Ireland, especially as both remain significantly contested, but a continued focus on these inherited scales has hindered critical attention to transnational routes and roots that exist alongside and challenge the nation. This volume sets agenda for the future of study of transnationalism in Irish literature and culture, recognizing the need for a new set of theories and methodologies that are adequate to our emerging world